CHANGES IN LAW IN CONDITIONS OF PUBLIC MODERNIZATION: HISTORY AND MODERNITY - V. V. Denisenko (Теоретическая и прикладная юриспруденция)
The article is devoted to changes in law in the process of social modernization. The historical analysis of changes in legal procedures in the process of historical formation of modern society is carried out. The factors of changes in modern legal systems and in the legal systems of the past are revealed. The article uses the methods necessary for the doctrinal analysis of changes in law, namely: formal-legal, as well as comparative-legal and concrete historical. The result of the study was the analysis and author’s conclusions about legal regulation and legal policy in a postmodern society.